Large-scale synthesis of ZIF-67 and highly efficient carbon capture using a ZIF-67/glycol-2-methylimidazole slurry. (1st December 2015) - Pan, Yong; Li, Hai; Zhang, Xiao-Xin; Zhang, Zhe; Tong, Xiong-Shi; Jia, Chong-Zhi; Liu, Bei; Sun, Chang-Yu; Yang, Lan-Ying; Chen, Guang-Jin
Abstract: New approaches and materials for inexpensive carbon capture are important areas of research. Herein, we report a new material (i.e., zeolitic imidazolate framework-67 (ZIF-67)/glycol-2-methylimidazole (mIm) slurry) that can be used to capture CO2 similar to a liquid absorbent, and ZIF-67 was synthesized on a pilot scale. This flowable slurry was formed by suspending ZIF-67 in a glycol–mIm solution. The results from the gas-–slurry equilibrium experiments indicate that this method provides a more efficient approach for the low cost capture of CO2 compared to conventional technologies. The selectivities for CO2 /H2, CO2 /N2, and CO2 /CH4 were 1409, 723, and 222, respectively. The apparent solubility of CO2 in the slurry was 1.3 mol L −1, and the sorption enthalpy was only −33 kJ mol −1 at 1 bar and 303.2 K. To simulate an actual separation process for carbon capture using the ZIF-67/glycol–mIm slurry, a series of column breakthrough tests were performed in a stainless steel bubbling column to investigate the influence of temperature, ZIF-67 mass fraction in the slurry, feed gas flow rate, and composition. The slurry was completely regenerated via helium purging and heating at 323–343 K. The CO2 capture ability of the regenerated slurry was the same as that of the fresh slurry, even after 10 adsorption/desorption cycles. Graphical abstract: Highlights: A novel absorption–adsorption hybrid method with ZIF-67/glycol–mIm slurry was developed to capture CO2 . The selectivities for CO2 /H2, CO2 /N2, and CO2 /CH4 exceed that needed for an efficient separation. The apparent solubility of CO2 in the slurry reaches 1.3 mol L −1 at 1 bar and 303.2 K. The slurry could be completely regenerated and the sorption enthalpy is only −33 kJ/mol.